1997
DOI: 10.1086/304261
|View full text |Cite
|
Sign up to set email alerts
|

The Homogeneity of Spheroidal Populations in Distant Clusters

Abstract: The small scatter observed for the (U[V ) colors of spheroidal galaxies in nearby clusters of galaxies provides a powerful constraint on the history of star formation in dense environments. However, with local data alone, it is not possible to separate models where galaxies assembled synchronously over redshifts 0 \ z \ 1 from ones where galaxies formed stochastically at much earlier times. Here we attempt to resolve this ambiguity via high-precision rest-frame UVÈoptical photometry of a large sample of morpho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
480
7
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(553 citation statements)
references
References 59 publications
62
480
7
1
Order By: Relevance
“…Detailed studies of elliptical galaxies in nearby and intermediate redshift clusters showed that their photometric properties are homogeneous and evolve only mildly with redshift at z ∼ < 1. This is consistent with the so-called 'passive evolution', namely the change of the photometric properties of elliptical galaxies by the aging of their stars only, with a formation epoch of at least ∼ 10 Gyr ago (Bower, Lucey & Ellis 1992;Aragón-Salamanca et al 1993;Ellis et al 1997;Dickinson 1997b;Stanford, Eisenhardt, & Dickinson 1997). On the other hand, some S0 and spiral galaxies seem to experience faster evolution (e.g., Dressler et al 1994;Dressler and Smail 1997).…”
Section: Introductionsupporting
confidence: 78%
“…Detailed studies of elliptical galaxies in nearby and intermediate redshift clusters showed that their photometric properties are homogeneous and evolve only mildly with redshift at z ∼ < 1. This is consistent with the so-called 'passive evolution', namely the change of the photometric properties of elliptical galaxies by the aging of their stars only, with a formation epoch of at least ∼ 10 Gyr ago (Bower, Lucey & Ellis 1992;Aragón-Salamanca et al 1993;Ellis et al 1997;Dickinson 1997b;Stanford, Eisenhardt, & Dickinson 1997). On the other hand, some S0 and spiral galaxies seem to experience faster evolution (e.g., Dressler et al 1994;Dressler and Smail 1997).…”
Section: Introductionsupporting
confidence: 78%
“…The epoch of galaxy formation has been chosen in order to satisfy the observations (e.g. Ellis et al 1997) showing that ellipticals in dense clusters stopped most of their star formation before z∼ 2.5 − 3. In this way we have a small formation period (as suggested by the tightness of the color-magnitude relation, e.g.…”
Section: Model Resultsmentioning
confidence: 99%
“…Their ubiquitous colour-magnitude sequence, first noted locally by Baum (Baum 1959), is now well documented in many clusters, ranging from Coma to clusters at redshifts up to z = 1 (Stanford, Eisenhardt, & Dickinson 1998, Ellis et al 1997, Gladders & Yee 2000. The colours of elliptical galaxies become bluer as they become less luminous.…”
Section: Galaxy Colours and Estimating Photometric Redshiftsmentioning
confidence: 87%